The Optimal Maturation of Subcutaneous Pouch Can Improve Pancreatic Islets Engraftment in Rat Model - Patikova, Alzbeta; Vojtiskova, Alzbeta; Fabryova, Eva; Kosinova, Lucie; Heribanová, Andrea; Sticova, Eva; Berkova, Zuzana; Hladikova, Zuzana; Kriz, Jan (Transplantation, 2022)
BACKGROUND: Transplantation of pancreatic islets into subcutaneous cavities in diabetic rats may be as or even more effective than transplantation into the portal vein. Identifying the optimal timing of the individual steps in this procedure is critical. METHODS: Macroporous scaffolds were placed in the subcutaneous tissue of diabetic male Lewis rats for 7 or 28 d and the healing of the tissue inside the scaffolds was monitored. A marginal syngeneic graft comprising 4 islets/g of recipient body weight was transplanted at the best timing focusing mainly on vascularization. Recipients were monitored for blood glucose levels and tolerance tests. Histological examination was performed in all implanted scaffolds. The presence of individual endocrine cells was analyzed in detail. RESULTS: Blood glucose levels remained within the physiological range in all recipients until the end of experiment as well as body weight increase. Coefficients of glucose assimilation were normal or slightly reduced with no statistically significant differences between the groups 40 and 80 d after transplantation. Histological analysis revealed round viable islets in the liver similar to those in pancreas, but alpha cells practically disappeared, whereas islets in the scaffolds formed clusters of cells surrounded by rich vascular network and the alpha cells remained partially preserved. CONCLUSIONS: Subcutaneous transplantation of pancreatic islets is considerably less invasive but comparably efficient as commonly used islet transplantation into the portal vein. In consideration of alpha and beta cell ratio, the artificial subcutaneous cavities represent a promising site for future islet transplantation therapy.
Keywords: krysa rodu Rattus; Animals; Islets of Langerhans Transplantation; experimentální diabetes mellitus; potkani inbrední LEW; Langerhansovy ostrůvky; Islets of Langerhans; Subcutaneous Tissue; Blood Glucose; zvířata; mužské pohlaví; subkutánní tkáň; Male; krevní glukóza; Rats, Inbred Lew; Rats; transplantace Langerhansových ostrůvků; Diabetes Mellitus, Experimental